2000
DOI: 10.1063/1.480576
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of the O(3P)+CH4→OH+CH3 reaction: An application of the rotating bond umbrella model and spectral transform subspace iteration

Abstract: We have applied the rotating bond umbrella ͑RBU͒ model to perform time-independent quantum scattering calculations of the O( 3 P)ϩCH 4 →OHϩCH 3 reaction based on a realistic analytic potential energy surface. The calculations are carried out in hypercylindrical coordinates with a log-derivative method incorporating a guided spectral transform ͑GST͒ subspace iteration technique. A single sector hyperspherical projection method is used for applying the boundary conditions. The results show that ground-state CH 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 66 publications
4
35
4
Order By: Relevance
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
“…[8][9][10][11]15,[20][21][22][23][24][25]35,[39][40][41][42][43][44] The most elaborate calculations included six to seven degrees of freedom explicitly. The most detailed results can be obtained when reactions involving only few atoms are studied in gas phase or molecular beams.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] There have also been studies on bend-excitation in the O + CH 4 reaction. [18][19][20] However, apart from very recent computational studies on the F + CH 4 ͑v 4 =1͒ and F + CH 2 D 2 ͑v 9 =1͒ reactions, 21,22 the previous work usually focused on the late-barrier polyatomic reactions ͑the transition state has a product-like structure͒ and there is almost no prior study on bending-excited early-barrier reactions, such as the F + methane reaction. Indeed the Polanyi rules 23 predict that the translational energy is more efficient to activate early-barrier reactions than vibrational excitation ͑and the reverse is true for the late-barrier reactions͒.…”
mentioning
confidence: 99%